Zero hour eaudiobook - Cussler, Clive (NUMA Files, 2016)
A #1 New York Times bestselling author and creator of the wildly popular Dirk Pitt series, Clive Cussler joins forces with acclaimed writer Graham Brown in Zero Hour , a thrilling adventure from the NUMA Files. After a scientist discovers how to harvest zero point energy, Kurt Austin, Joe Zavala, and the rest of the NUMA team must race to stave off a catastrophe.